Pacing Lead-Induced Granuloma in the Atrium: A Foreign Body Reaction to Polyurethane - Shinagawa Yoko; Yuka Kobayashi; Takao Iiri; Hitoshi Kitazawa; Masaaki Okabe; Hiroshi Kobayashi; Etsuo Okazaki; Yoshifusa Aizawa (Case Reports in Cardiology)
We described a case of an 82-year-old male who presented with a granuloma entrapping the polyurethane-coated pacing lead at the site of contact on the atrium. He had been paced for 8 years without symptoms or signs suggestive of an allergic reaction to the pacemaker system and died from thrombosis of the superior mesenteric artery and heart failure. A histological examination of the nodule showed an incidental granuloma with multinucleated giant cells. No granuloma was found in the heart or the lung.